PENGARUH GUGUS KENDALI MUTU (GKM) DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DI DEPARTEMENT ENGINEERING WORK SHOP PT. MULIAKERAMIK INDAHRAYA Tbk. CIKARANG - Supriatin Supriatin (Universitas Bina Sarana Informatika, 2018)
ABSTRACKQuality Control Cycle ( QCC ) is one method or program empowering employees to improve productivity . In this case , the Department of Work Shop Engineering PT . Muliakeramik Indahraya TBk , every year regularly convened Quality Control Circle ( QCC ) and also strengthening the work culture with the exercises of self-motivation to employees to improve employee performance . In that regard the author is interested in conducting research on this subject . Riser using quantitative methods with multiple linear regression , with a sample of 60 respondents. From the shows results that there is influence between the Quality Control Circle ( QCC ) and the Employee Performance Work Culture with less significant results , with the value of determination ( R ² ) were very minimal , namely 0.007 . But normality test each variable significantly greater than 0.005